Long‐term outcomes of esophageal squamous cell carcinoma with invasion depth of pathological T1a‐muscularis mucosae and T1b‐submucosa by endoscopic resection followed by appropriate additional treatment. Issue 4 (20th October 2021) - Naito, Sakiko; Yoshio, Toshiyuki; Ishiyama, Akiyoshi; Tsuchida, Tomohiro; Tokura, Junki; Namikawa, Ken; Tokai, Yoshitaka; Yoshimizu, Shoichi; Horiuchi, Yusuke; Hirasawa, Toshiaki; Asari, Takao; Mine, Shinji; et al.
Abstract : Objectives: Endoscopic resection (ER) is indicated for a wide range of superficial esophageal squamous cell carcinomas (ESCCs). We examined the long‐term outcomes in patients with pathological (p) invasion of ESCC into the T1a‐muscularis mucosae (MM) and T1b‐submucosa (SM) after ER, for which data on prognosis are limited. Methods: Of the 1217 patients with superficial ESCC who underwent ER, 225 patients with a pathological diagnosis of ESCC invasion into the MM, minute submucosal invasion ≤200 µm (SM1), or massive submucosal invasion (SM2) were included. In patients with lymphovascular invasion, droplet infiltration, or SM2 invasion, additional treatments, including chemoradiation (CRT) or esophagectomy with two‐ to three‐field lymph node dissection, were recommended. The median observation period was 66 months (interquartile range 48–91 months). Results: In total, there were 151, 28, and 46 pT1a‐MM, pT1b‐SM1, and pT1b‐SM2 cases, respectively. Metastatic recurrence was observed in 1.3%, 10.7%, and 6.5% patients with pT1a‐MM, pT1b‐SM1, and pT1b‐SM2 ESCCs, respectively. Of the eight patients with metastatic recurrence, six were successfully treated, and two died of ESCC. The 5‐year overall survival rates were 84.1%, 71.4%, and 67.4%, the 5‐year relapse‐free survival rates were 82.8%, 64.3%, and 65.2%, and the 5‐year disease‐specific survival rates were 100%, 96.4%, and 99.1% in patients with pT1a‐MM, pT1b‐SM1, and pT1b‐SM2 ESCCs, respectively. Multivariate analysis showed that additional CRT and esophagectomy, and T1b‐SM2 were positively and negatively associated with overall survival, respectively. Conclusions: Endoscopic resection preceding appropriate additional treatments resulted in favorable outcomes. Many cases of metastatic recurrence in this cohort could be successfully treated.